Arbuscular mycorrhizal fungi as mediators of ecosystem responses to nitrogen deposition: A trait‐based predictive framework. (13th February 2018) - Treseder, Kathleen K.; Allen, Edith B.; Egerton‐Warburton, Louise M.; Hart, Miranda M.; Klironomos, John N.; Maherali, Hafiz; Tedersoo, Leho
Abstract: Anthropogenic nitrogen (N) deposition is exposing plants and their arbuscular mycorrhizal fungi (AMFs) to elevated N availability, often leading to shifts in communities of AMF. However, physiological trade‐offs among AMF taxa in their response to N enrichment vs the ability to acquire other soil nutrients could have negative effects on plant and ecosystem productivity. It follows that information on the functional traits of AMF taxa can be used to generate predictions of their potential role in mediating ecosystem responses to N enrichment. Arbuscular mycorrhizal fungi taxa that produce extensive networks of external hyphae should forage for N and phosphorus (P) more effectively, but these services incur greater carbon (C) costs to the plant. If N enrichment ameliorates plant nutrient limitation, then plants may reduce C available for AMF, which in turn could eliminate AMF taxa with large extensive external hyphae from the soil community. As a result, the remaining AMF taxa may confer less P benefit to their host plants. Using a synthesis of data from the literature, we found that the ability of a taxon to persist in the face of increasing soil N availability was particularly high in isolates from the genus Glomus, but especially low among the Gigasporaceae. Across AMF genera, our data support the prediction that AMF with a tolerance for high soil N may confer a lower P benefit to their host plant. Relationships between high N tolerance and production of external hyphae were mixed. Synthesis . If the relationship between N tolerance and plant P benefit is widespread, then shifts in arbuscular mycorrhizal fungi communities associated with N deposition could have negative consequences for the ability of plants to acquire P and possibly other nutrients via a mycorrhizal pathway. Based on this relationship, we predict that arbuscular mycorrhizal fungi responses could constrain net primary productivity in P‐limited ecosystems exposed to N enrichment. This prediction could be tested in future empirical and modelling studies. Abstract : If the relationship between N tolerance and plant P benefit is widespread, then shifts in arbuscular mycorrhizal fungi communities associated with N deposition could have negative consequences for the ability of plants to acquire P and possibly other nutrients via a mycorrhizal pathway. Based on this relationship, we predict that arbuscular mycorrhizal fungi responses could constrain net primary productivity in P‐limited ecosystems exposed to N enrichment. This prediction could be tested in future empirical and modelling studies.